Creating meaningful learning opportunities for children with Cerebral Palsy in South African rural schools - Steyn, Miemsie G. (University of Pretoria, 2018)
Inclusive education is a strategy aimedat ensuring equal education for all children, regardless of race, colour, gender or ability. Many countries internationally are in the process of implementing this approach, but progress has been much slower in developing countries such as South Africa. Challenges of implementation are, among others, attributed to the Western origin of this approach, with the result that more than twenty years after its conceptualisation, little progress has been made. Even after the implementation of inclusive education, children with disabilities, particularly those with cerebral palsy, are still being excluded from accessing the general curriculum in rural schools; neither is teacher training sufficient in equipping teachers with the necessary skills to teach children with diverse educational needs in inclusive classes; therefore, children with cerebral palsy experience numerous barriers totheir academic progress compared to children without disabilities. It is, thus, the aim of this research study to use Bronfenbrenner’s Ecological Systems Theory as a theoretical lens in order to elicit qualitatively the perceptions of rural school teachers towards inclusive education and how to teach children with cerebral palsy in those schools. Piaget’s theory of cognitive development and Vygotsky’s social constructivist theory are used as accompanying theories to reviewthe development of children with cerebral palsy and the support they require to progress in rural schools. The empirical data collected have provided rich insight in informing factors to improve curriculum accessibility for children with cerebral palsy and to facilitate the implementation of inclusive education in rural schools.